Basic principles of descriptive statistics in medical research - N. M. Bulanov; A. Yu. Suvorov; O. B. Blyuss; D. B. Munblit; D. V. Butnaru; M. Yu. Nadinskaia; A. A. Zaikin (Сеченовский вестник, 2021)
Descriptive statistics provides tools to explore, summarize and illustrate the research data. In this tutorial we discuss two main types of data - qualitative and quantitative variables, and the most common approaches to characterize data distribution numerically and graphically. This article presents two important sets of parameters - measures of the central tendency (mean, median and mode) and variation (standard deviation, quantiles) and suggests the most suitable conditions for their application. We explain the difference between the general population and random samples, that are usually analyzed in studies. The parameters which characterize the sample (for example, measures of the central tendency) are point estimates, that can differ from the respective parameters of the general population. We introduce the concept of confidence interval - the range of values, which likely includes the true value of the parameter for the general population. All concepts and definitions are illustrated with examples, which simulate the research data.